Stunting in Toddlers (6-60 Months): Parenting Pattern, Mother's Education Level, Infectious Diseases, and Breastfeeding - Kasmita Kasmita; Nabila Tasrif; Titen Darlis Santi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Stunting is a form of failure to thrive which reflects chronic and multidimensional nutritional problems. This study aims to analyze the relationship between a mother's education level, exclusive breastfeeding, and a history of infectious disease on stunting at the age of toddlers (6-60) months. The research design was cross-sectional with a purposive sampling technique. This study was conducted on mothers who have toddlers aged (6-60) months in the working area of the Seberang Padang Health Center as many as 60 people. Data collection techniques in this study were through survey methods and direct interviews with mothers who have toddlers. Data were analyzed using the chi-square test. The results showed a significant relationship between exclusive breastfeeding (p-value = 0.001; 0.067) and a history of infectious disease (p-value = 0.028; 0.218) with stunting. However, there is no significant relationship between a mother’s education level and stunting. This research can be said that exclusive breastfeeding and a history of the disease are the risks of stunting. The need for special attention and improvement of health promotion and education programs for the Seberang Padang Health Center in preventing stunting in toddlers.